Analisis Pengaruh Lingkungan Kerja, Disiplin, Motivasi, dan Gaya Kepemimpinan terhadap Produktivitas Karyawan - -, Sutinem sutinem (Politeknik Negeri Padang, 2025)
This research aims to analyze the influence of the working environment, work discipline, work motivation on productivity through leadership styles as intervening variables. The research sample consists of 100 teachers working at public schools in Lamongan. Sampling is by using a saturated sample of the entire population. The data analysis technique is using SEM PLS from the PLS ver 3 smart application. The results of the study were: (1) the influence of the working environment on the leadership style is significant, (2) the impact of the work discipline on the management style is non-significant, (3) the effect of the motivation of the job on the style of leadership is insignificant,(4) the impact on the productivity of the labour environment is significant; (5) the effects of the labor discipline upon the productiveness is not significant; (6) the influences of the employment motivation on the production style are not significant, (7) the influencing of the leadage style upon the production of the productive style is nonexistent; (7) the impacts of the employing environment on production through leadership are not significant; (8) the influencies of the disciplinary work on productiveness through the lead ability style are non-substantial; (9) the influencer of the training discipline over productivity through the leading style is not important; (10) the influency of work motivation upon productive mode is not substantial.